Study on salt-tolerant and drought-tolerant characteristics of Bacillus velezensis ZX101 - Cui Zhihao; Liu Hui (BIO Web of Conferences)
To explore the salt tolerance and drought resistance characteristics of B. velezensis ZX101, this study investigates the potential of the strain to thrive in adverse environmental conditions. By analyzing the effects of different NaCl concentrations and salinity on the growth of the strain, the study examines the impact of NaCl concentration on the intracellular protein content, soluble sugar content, and relative permeability of the cell membrane. Additionally, the growth conditions of the strain in a simulated drought environment with different additions of PEG6000 are explored. The results indicate: (1) Increased NaCl concentrations prolong the lag phase and reduce biomass; (2) In addition to NaCl, strain ZX101 can also tolerate other salts such as NaNO2, KCl, MgCl2, and CaCl2; (3) As NaCl concentration increases, the intracellular protein content and soluble sugar content increase, and cell permeability rises from 13.63% to 31.45%; (4) Enhanced drought stress slows down the growth of the strain, but overall, it can resist severe drought stress, potentially due to spore formation. Conclusion: Strain ZX101 could provide a theoretical basis for abiotic stress agricultural solutions based on rhizobacteria.